Thermal Performance and energy savings of a ground -sink heat pump for air conditioning system - Rosniah Binti Che Abdullah (School of Environmental Engineering University Malaysia Perlis, 2011)
This study reports a thermal performance and energy savings between a ground-sink heat pump (GSHP) system and an air-sink heat pump (ASHP) systems. The systems connected to a test room in the School of Environmental Engineering, University Malaysia Perlis , were designed and constructed for space cooling. The performances of GSHP and the ASHP system were experimentally determined. The experimental results were obtained from 22 to March 2011 in hot humid climate for which the data taken every 15 minutes in 12 hours a day. The average coefficient of performance (COP) was determined using the measured absolute temperature of the cooled space and heat sinks.